The space between a textual analysis of the representation of the tween identity through romance in GMA-7's Tween Hearts - Pasion, Patricia Anne D. 1992- (2012)
"This research study aimed to identify how the tween identity was represented through the use of element of romance in the narratives of the youth-oriented show, Tween Hearts. Youth-oriented shows have been popular in the Philippines since the late 1990's and the early 2000's featuring love, relationships and friendships among the youth aged 17-20 years old. Tween Hearts tackles issues and concerns of being a tween which is a younger age group ranging from 8-15 years old. The study used textual analysis of 20 episodes of the first season of the program. The manifestations of love in the program were identified through Gary Chapman's Five Languages of Love. The tween identity was zeroed in using the research of Maria Theresa Ujano-Batangan, Ph.D. on adolescents. Interviews with the executive producer and the head writer of the program were also conducted to understand how the adult producers of Tween Hearts write content for the youth. The frameworks used in the study were Hall's theories on encoding, representation and identity. Psychological concepts on development as well as political economy perspective were incorporated in the analysis of the data.The study revealed that the tweens were represented as individuals whose identity are always in the process of change in terms of acts, behaviors and experimenting with new things. And in this process, love was the catalyst that aided in representing and pursuing such changes. The presence of love and the parallelism of the characters to the real lives of the tween celebrities denoted the building up of the image of the young artists. This signified that commercial interest was a prime factor in constructing the tween identity, as represented in the show."